2021
DOI: 10.1097/ta.0000000000003207
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic shock model on the effect of endothelial aging on vascular barrier properties

Abstract: BACKGROUND:Aging is characterized by a decline in cellular function, which has an adverse effect on the biologic response to injury. Both aging and trauma/ hemorrhagic shock (T/HS) increase oxidative stress which impairs the vascular endothelium (EC) and glycocalyx (EG). The additive effect of aging on EC and EG damage following T/HS are unknown. This was studied in an in vitro model. METHODS:Confluent endothelial cell monolayers from primary aortic endothelial cells from 10-week-old mice ("young" cells) or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…EG is the main functional barrier to the vascular endothelium and plays an important role in maintaining selective vascular permeability [ 137 ]. Decreased microvascular density and loss of EG have been found during the aging process [ 51 ]. It has been shown in previous experiments that EG deficiency is closely linked to age-related diseases, thus protecting and repairing the EG is essential for healthy aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EG is the main functional barrier to the vascular endothelium and plays an important role in maintaining selective vascular permeability [ 137 ]. Decreased microvascular density and loss of EG have been found during the aging process [ 51 ]. It has been shown in previous experiments that EG deficiency is closely linked to age-related diseases, thus protecting and repairing the EG is essential for healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SA is degraded from erythrocyte membranes at a higher rate in older adults compared to young adults, which may be associated with the increase in oxidative stress during aging [ 50 ]. In vitro study also has shown that aged cells have increased EG shedding and decreased EG layers, and under biomimetic shock conditions, EG shedding is further exacerbated in aged as compared to young endothelial cells [ 51 ]. Human brain is one of the two most abundant tissue sources of KS, and KS has neuroregulatory properties [ 52 , 53 ].…”
Section: Eg In Aging and Age-related Diseasesmentioning
confidence: 99%
“…Likewise, early use of VHAs in SIC enables early detection of the depth and duration of shock prior to coagulopathic manifestation by conventional coagulation tests (CCTs) and other standard clinical and biologic markers (Pavoni et al, 2020). Combined with CCTs, VHAs, and clinical and laboratory markers such as lactate and procalcitonin, a PBM approach to assess the depth and duration of shock is becoming a reality whether in TIC or SIC (Vorweg et al, 2013;Müller et al, 2014;Saraiva et al, 2016;Johansson et al, 2017a;Martínez et al, 2018;Stettler et al, 2019;Walsh et al, 2020b;Scarlatescu et al, 2020;Carge et al, 2021;Drost et al, 2021;Pape et al, 2021;Tuan et al, 2021;Bunch et al, 2022a).…”
Section: Pathophysiology Of Shinementioning
confidence: 99%
“…Vascular aging, an important cardiovascular risk factor associated with increased vessel stifness, is characterized by microvascular dysfunction, impaired perfusion and reduced capillary density (106). In mice, glycocalyx thickness and integrity are reduced with age (107,108). A reduction of the endothelial glycocalyx thickness of ∼30% was observed also in humans with a mean age of 60 years compared to 30-year-old individuals (109).…”
Section: Endothelial Glycocalyx Damage and Its Link To Risk Factors O...mentioning
confidence: 99%